Réponses

2014-10-07T10:29:11+02:00
1)
5x + 3y = 1
2x + y = 3

5x + 3y = 1
- 6x - 3y = - 9
- x = - 8
x = 8

2x + y = 3
2 * 8 + y = 3
16 + y = 3
 y = 3 - 16
y = - 13

Les solutions sont : (8 ; - 13)

Tu fais pareil pour l'autre

2)
4t + 3y - 11 = 0
3t - 2y = 4

8t + 6y - 22 = 0
9t - 6y = 12

17t - 22 = 12
17t = 12 + 22
17t = 34
t = 34/17
t = 2

3t - 2y = 4
3 * 2 - 2y = 4
6 - 2y = 4
- 2y = 4 - 6
- 2y = -2
y = 2/2
y = 1

Les solutions sont : (2 ; 1)

Tu fais pareil pour l'autre

3)
0,8x + 2y/3 = 2
6x + 5y = 15

2,4x/3 + 2y/3 = 6/3
2,4x + 2y = 6

2,4x + 2y = 6
12 + 10y = 10
- 12x - 10y = 12

- 2x =22
x = - 22/2
x = 11

6x + 5y = 15
6 * 11 + 5y = 15
66 + 5y = 15
5y = 15 - 66
5y = - 51
y = - 51/5
y = - 10,2

Les solutions sont ; (11 ; - 10,2)

Je te laisse faire l'autre